Study of the concept of detention in theater’s Jean -Paul Sartre: No Exit and the condemned of Altona - Hussein, Thakaa Muttib (Al-Adab Journal, 2021)
The two plays, No Exit and The Condemned of Altona, are works of modern French theater. The author presents the detainee’s suffering and his relationship with others within a specific reality and time circumstance. In the first chapter, we review the play of a closed session and the story of three criminal suspects living their fate after death in Hell in a strange and unimaginable atmosphere. As for the play the Condemned of Altona, the writer portrays the tragedy of a generation of young people after World War II as they live the tragedy of their actions that they took against humanity during the war. In the second chapter, we examine the study of the pre-detention period and the world of memories, in order to reach the reality of the events separating the detainee between his past and present, once with himself and the other with others. In the third chapter, we examine the detention between illusion and reality, and that the detainee in theater’s Sartre is nothing but confined to others' view of what he is doing and how voluntary detention will ultimately be the existential act. And how that encourages the individual to make conscious choice embodied in personal freedom to commit and acknowledge his actions to the end of his life.